1995
DOI: 10.1046/j.1471-4159.1995.65062652.x
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Glutamylglutamine and Taurine Concentrations Are Decreased in the Cerebrospinal Fluid of Drug‐Naive Patients with Schizophrenic Disorders

Abstract: HPLC and gas chromatography-mass spec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 31 publications
1
30
1
2
Order By: Relevance
“…Whether the difference in plasma taurine levels in females depends on the menstrual cycle or on the illness cannot be elucidated from our data. In contrast to Do et al (1995), who found lower taurine levels in the CSF in unmedicated patients with schizophrenia compared with controls, we found no statistically significant differences. Because the patients in our study were medicated and well-controlled outpatients, the mild degree of the disorder found might have an impact on the taurine levels in the CSF.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Whether the difference in plasma taurine levels in females depends on the menstrual cycle or on the illness cannot be elucidated from our data. In contrast to Do et al (1995), who found lower taurine levels in the CSF in unmedicated patients with schizophrenia compared with controls, we found no statistically significant differences. Because the patients in our study were medicated and well-controlled outpatients, the mild degree of the disorder found might have an impact on the taurine levels in the CSF.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies, in both blood and CSF, indicate that taurine and GSH levels are altered in patients with schizophrenia compared to healthy individuals (Bjerkenstedt et al, 1985;Rao et al, 1990;Do et al, 1995Do et al, , 2000Raffa et al, 2009). In previous studies, we found complex associations between the taurine (Samuelsson et al, 2009) andGSH (Samuelsson et al 2011) levels in plasma and CSF in healthy men.…”
Section: Introductionmentioning
confidence: 55%
“…Further supportive evidence is provided by a study reporting a 27 % reduction in the CSF glutathione level in neuroleptic-naive patients with schizophrenia compared with controls, which coexisted with a 52 % glutathione reduction in the medial prefrontal cortex, as measured by magnetic resonance spectroscopy (Do et al, 2000). The low CSF glutathione appears to be consistent with previous findings of decreased levels of its metabolite, c-glutamylglutamine, in the CSF of schizophrenia patients (Do et al, 1995).…”
Section: Assays Of Oxidants and Antioxidantssupporting
confidence: 77%
“…Taurine deficiency in development leads to abnormal cerebellar organization and function. Reduced levels of CSF taurine lave been demonstrated in drug-free schizophrenic patients (Do et al, 1995).…”
Section: Discussionmentioning
confidence: 99%